(untitled) (Journal of Atomic and Molecular Sciences, 2021)
The Loschmidt echo of single qubit coupling to the environment for dimerized anisotropic XY spin chain in transverse field have been analyzed. We have obtained analytical expression for the Loschmidt echo. By numerically computing the Loschmidt echo, we find that the decay of coherence will be enhanced with the increasing of the staggered parameter.